Surface Effects on the Dynamic Behavior of Vortices in Type II Superconducting Strips with Periodic and Conformal Pinning Arrays - Vizarim, N. P. [UNESP]; Carlone, M. [UNESP]; Verga, L. G.; Venegas, P. A. [UNESP] (Springer Nature, 2018)
Using molecular dynamics techniques, we simulate the vortex behavior in a type II superconducting strip in the presence of triangular and two types of conformal pinning arrays, one with a pinning gradient perpendicular to the driving force (C1) and the other parallel (C2), at zero temperature. A transport force is applied in the infinite direction of the strip, and the magnetic field is increased until the rate between the density of vortices (nv) and pinning (np) reaches nv/np = 1.5. Our results show a monotonic increase, by steps, of the vortex density with the applied magnetic field. Besides, each pinning lattice presents a different vortex penetration delay. For the triangular pinning array, different than the case of infinite films, here the system exhibits only one pronounced depinning force peak at nv/np = 1. However, the depinning force peak is present for only one value of field, in the range of fields where nv/np = 1 is stable. For the case of conformal pinning arrays, in analogy to what is observed in infinite films, no commensurability depinning force peaks were found. In the present case, the C1 array is more efficient at low fields, all arrays are equivalent in the intermediate fields, and the C2 array is more efficient for high fields. We also show that for the C1 array at high fields, vortices depin following the conformal arches, from the edge to the center. For the C2 array, the depinning force is higher when compared to that of C1, because this particular conformal structure prevents the formation of easy vortex flow channels.
Keywords: Conformal pinning; Periodic pinning; Superconductivity; Surface effects; Vortex dynamics